Pore Pressure Pulse Drove the 2012 Emilia (Italy) Series of Earthquakes. Issue 2 (24th January 2018) - Pezzo, Giuseppe; De Gori, Pasquale; Lucente, Francesco Pio; Chiarabba, Claudio
Abstract: The 2012 Emilia earthquakes sequence is the first debated case in Italy of destructive event possibly induced by anthropic activity. During this sequence, two main earthquakes occurred separated by 9 days on contiguous thrust faults. Scientific commissions engaged by the Italian government reported complementary scenarios on the potential trigger mechanism ascribable to exploitation of a nearby oil field. In this study, we combine a refined geodetic source model constrained by precise aftershock locations and an improved tomographic model of the area to define the geometrical relation between the activated faults and investigate possible triggering mechanisms. An aftershock decay rate that deviates from the classical Omori‐like pattern and Vp / Vs changes along the fault system suggests that natural pore pressure pulse drove the space‐time evolution of seismicity and the activation of the second main shock. Plain Language Summary: Induced seismicity has increasingly become a major topic among Earth scientists. Concerns about a causative role played by the oil‐gas extraction and/or the deep injection of disposable water in triggering earthquakes have grown fast in recent years, with many implications for public regulators and stakeholders. We present and discuss the 2012 Emilia (Italy) earthquakes sequence, which is the first debated case in Italy of destructive events possibly induced by anthropic activity. We use coseismic ground deformation measurements and seismic data to define the geometrical relation between the activated faults and investigate possible triggering mechanisms. Our results indicate that fluid pressure at the base of the system was responsible for triggering the two 2012 main earthquakes and exclude any anthropic trigger. Thus, cautious monitoring of seismicity, deformation, and pore pressure can recognize active processes along active faults that can potentially cause earthquakes. Such monitoring should be mandatory to conjugate exploitation activity in seismic active areas with safeness and sustainability. Key Points: Refined fault geometries using precise aftershock relocation and updated coseismic and aseismic slips for the Emilia main shocks Aftershock decay rate deviates from classical Omori‐like pattern and Vp / Vs changes along the fault system during the sequence Fluid pressure pulse drove the seismic sequence and triggered the second main shock